The Correlation Between Students Self-Confidence and Speaking Ability ( A Correlation Study at SMAN 11 Banda Aceh) - Salsabila Salsabila; Zaiyana Putri; Muchsin Muchsin (UNIVERSITAS SERAMBI MEKKAH, 2023)
The aim of this research is to find out if there is a positive correlation between students self-confidence and speaking ability. The students self-confidence was variable X and speaking ability was variable Y. This study was focused on the problems on the correlation between student self-confidence and speaking ability. This research was conducted based on the correlation research design. The participants of this study were students at SMAN 11 Banda Aceh. It was the eleven grade female students, which was from the class of XI IA3. This class consists of 30 students. In collecting the data, the researcher used two methods to collect the data of two variables. The instruments were a questionnaire and speaking test. The first instrument is a questionnaire, which contains 14 points. This questionnaire used to measure the level of students self-confidence. The second instrument is the speaking test. Oral proficiency scoring categories from Brown (2004) have been used as guidance to measure students' speaking ability by conducting “Invitation” as the topic. In analyzing the data, the researcher correlated the result of the questionnaire and the result of the speaking test by needing a partner to do conversation moment correlations. The result of research showed the students self-confidence and their speaking test is 1.00. This value shows the result of this study is 1,00 0,36 are included in the positive category. So Ha is higher than 0, 05. H0 is rejected and Ha is accepted. So there is a positive correlation between students’ self-confidence and their speaking ability of students SMAN 11 Banda Aceh